Nasakom and Bhinneka Tunggal Ika: a New Reading of Sukarno’s Politics from Philosophical Perspectives - Binsasi, Norbertus Antoin; Zubaidi, Ahmad; Santoso, Heri (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
Nasakom and Bhinneka Tunggal Ika are Indonesian political terms that Indonesians and foreign researchers and observers know but still contain a lot of unclear understanding. This study wants to answer this ambiguity, by exploring the existence and essence of Nasakom and then linking it to Bhinneka Tunggal Ika, using philosophical methods. The aim is to find a